(untitled) (CIPEEX, 2022)
HUMAN IMMUNODEFICIENCY VIRUS (HIV) IS THE CAUSE OF ACQUIRED IMMUNODEFICIENCY SYNDROME (AIDS). THESE TERMS ARE NOT SYNONYMOUS AND THERE ARE MANY PATIENTS INFECTED WITH THE VIRUS WHO LIVE YEARS WITHOUT PRESENTING SYMPTOMS OR DEVELOP THE DISEASE, BUT CAN TRANSMIT THE VIRUS TO OTHER PEOPLE, ESPECIALLY UNPROTECTED SEX. THUS, THE USE OF PROPHYLACTIC MEDICATION, ESPECIALLY FOR HIGHER RISK GROUPS, IS ESSENTIAL. BRAZIL IS A REFERENCE IN HIV TREATMENT, AS IT WAS THE FIRST COUNTRY IN LATIN AMERICA TO OFFER FREE ANTIRETROVIRAL TREATMENT TO PEOPLE WITH THE VIRUS, AND PARTICIPATED IN THE PRE-EXPOSURE PROPHYLAXIS INITIATIVE (IPREX), A STUDY THAT PROVED THE EFFICACY OF PRE-EXPOSURE PROPHYLAXIS (PREP) WHICH INVOLVED SEVERAL OTHER COUNTRIES IN THE WORLD. THE USE OF MEDICATION FOR THE PREVENTION OF INFECTIONS, DISTRIBUTED BY THE PUBLIC SYSTEM, WHICH IS STILL LITTLE KNOWN BY THE POPULATION, IS INCLUDED IN THE STUDIES. THEREFORE, THE STUDY AIMS TO PRESENT THE POPULATION DEMAND, THE RISK GROUPS AND THE MOST USED DRUGS IN PREP. THIS IS AN EXPANDED SUMMARY, FROM 5 ARTICLES SELECTED IN THE PUBMED AND SCIENCE DIRECT DATABASES, USING THE DESCRIPTORS: PRE-EXPOSURE PROPHYLAXIS (PREP); HIV; PREVENTION; ANTIRETROVIRALS, WITH SELECTION OF ARTICLES PUBLISHED BETWEEN 2015 AND 2018. IT WAS CONCLUDED THAT THE USE OF PREP PRESENTED MEDIUM ADHESION AND REASONS FOR WITHDRAWAL, ESPECIALLY AMONG THE RISK GROUPS. FINALLY, AMONG THOSE TAKING ANTIRETROVIRALS, THERE WAS A RELATIONSHIP BETWEEN THE NUMBER OF HIV-INFECTED AND SEXUALLY TRANSMITTED DISEASES, AND DESPITE THE NUMERICAL ASSOCIATION, THERE IS NO PROVEN LINK.